Surgical Resection of Intraocular Tumors (Partial Transscleral Sclerouvectomy Combined With Mircoinvasive Vitrectomy and Reconstruction of the Eyeball) in Asian Patients: Twenty-Five Years Results - Zhou, Nan; Wang, Ping; Xu, Xiaolin; Liu, Yueming; Wei, Wenbin (Frontiers in Oncology, 2022)
Objective To describe the outcome of intraocular tumor resection by partial transscleral sclerouvectomy (PTSU) combined with micro-invasive vitrectomy and reconstruction of the eyeball (MVRE) in Asian patients. Design, Methods and Participants This retrospective, interventional cohort study included 366 patients who underwent PTSU combined with MVRE for intraocular tumors both in adult and pediatric age groups. The medical records of these patients were reviewed for clinical, operative, and histopathological features. Main Outcome Measures Globe salvage, best corrected visual acuity (BCVA), surgical side effects, tumor control, and tumor-related metastasis and death. Results The mean follow-up duration was 87 months (median, 66; range, 1-303 months). Among the 366 patients, the mean age was 8.5 years (median, 7; range, 1-19 years) in the 37 pediatric patients, and was 43 years (median, 42; range, 20-51) in 329 adult patients. The tumor mainly involved the ciliary body (n=136; 37.2%) and choroid (n=86; 23.5%). The common pathologic diagnosis of the 366 patients was as follows. In the pediatric age group, histopathologic examination revealed positive tumor margins in 37 patients mainly including ciliary body medulloepithelioma (8/37), ciliary body melanocytoma (13/37) and uveal melanoma (5/37). In the adult group, the pathological diagnosis mainly included melanoma (195/329), RPE adenoma (21/329), amelanotic melanoma (13/329), ciliary body adenoma of nonpigmented epithelium (19/329), schwannoma/neurilemmoma (11/329), melanocytoma (24/329), and leiomyoma (9/329). The globe salvage rate was 81.1% in the pediatric age groups (<20 years), and 93.6% in the adult group (≥20 years), respectively. Of the 338 salvaged eyes, final BCVA was 20/20 to 20/40 in 16 (4.7%), 20/40 to 20/80 in 58 (17.2%), 20/80 to 20/200 in 160 (47.3%), and ≤ 20/200 in 104 (30.8%). Early side effects included corneal edema in 28 (7.7%) patients, hyphema in 46 (12.6%), and vitreous hemorrhage in 76 (21%) patients. Postoperative side effects included proliferative vitreoretinopathy (PVR) in 67 (18.3%), late cataract in 42 (11.5%), and glaucoma in 18 (5%) patients. Local tumor recurrence was detected in 20 patients (5.5%) at a mean interval of 23.6 months, including melanoma (n=19) and medulloepithelioma (n=1). Enucleation was necessary in 28 (7.7%) cases owing to recurrence in 15 (53.6%), eye prophylaxis with high-grade malignancy in 5 (17.8%), and blind painful eye in 8 (28.6%) cases. Kaplan-Meier estimated for 5, 10-year metastasis rate and metastasis-related death rate (95%CI) in 213 UM patients were 3.2% (1.4%-7.0%), 6.9% (3.8%-12.3%); and 3.5% (1.6%-7.6%), 7.6% (4.2%-13.5%), respectively. Conclusions As a surgically challenging procedure, PTSU combined with MVRE offers several theoretical advantages over enucleation and radiotherapy. It can achieve control of most intraocular tumors, preserve useful vision, and maintain a cosmetically normal eye.